Nutritional and food aspects related to polioencephalomalacy in ruminant - Assis, J. R.; Assis, A. C. M.; Nunes, D.; Carlos, A. B. (Scientific Electronic Archives, 2020)
Polioencephalomalacia (PEM) is a nervous disease with neuronal necrosis. He previously believed that this condition was related to thiamine deficiency, but studies suggest that it can be determined by different nutritional and dietary factors. In this context, objectified to perform a literature review on the main causes of polioencephalomalacia caused by nutritional and dietary factors as well as the appropriate treatment and prevention in ruminants. Therefore, PEM disease can be caused by the classic thiamine deficiency, lead poisoning, sulfur and salt associated with drinking water deprivation. To prevent PEM, avoid contaminated material in pastures (avoid lead and sulfur), invasive plants (avoid thiaminases) and nutritional management of dietary thiamine concentrations and sulfur levels in water and diet. For treatment it is recommended to identify the source that causes the disease, deprivation of contaminated material and use of food management techniques, drugs needed to restore the metabolic parameters.